A complex secretory program orchestrated by the inflammasome controls paracrine senescence - Acosta, Juan-Carlos; Banito, Ana; Wuestefeld, Torsten; Georgilis, Athena; Janich, Peggy; Morton, Jennifer P.; Athineos, Dimitris; Kang, Tae-Won; Lasitschka, Felix; Andrulis, Mindaugas; Pascual, Gloria; Morris, Kelly J.; et al. (Nature cell biology, 2013)
Oncogene-induced senescence (OIS) is crucial for tumour suppression. Senescent cells implement a complex pro-inflammatory response termed the senescence-associated secretory phenotype (SASP). The SASP reinforces senescence, activates immune surveillance and paradoxically also has pro-tumorigenic properties. Here, we present evidence that the SASP can also induce paracrine senescence in normal cells both in culture and in human and mouse models of OIS in vivo. Coupling quantitative proteomics with small-molecule screens, we identified multiple SASP components mediating paracrine senescence, including TGF-β family ligands, VEGF, CCL2 and CCL20. Amongst them, TGF-β ligands play a major role by regulating p15INK4b and p21CIP1. Expression of the SASP is controlled by inflammasome-mediated IL-1 signalling. The inflammasome and IL-1 signalling are activated in senescent cells and IL-1α expression can reproduce SASP activation, resulting in senescence. Our results demonstrate that the SASP can cause paracrine senescence and impact on tumour suppression and senescence in vivo.